2010
DOI: 10.1016/j.stem.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Quiescent and Active Hippocampal Neural Stem Cells with Distinct Morphologies Respond Selectively to Physiological and Pathological Stimuli and Aging

Abstract: New neurons are generated in the adult hippocampus throughout life by neural stem/progenitor cells (NSCs), and neurogenesis is a plastic process responsive to external stimuli. We show that canonical Notch signaling through RBP-J is required for hippocampal neurogenesis. Notch signaling distinguishes morphologically distinct Sox2(+) NSCs, and within these pools subpopulations can shuttle between mitotically active or quiescent. Radial and horizontal NSCs respond selectively to neurogenic stimuli. Physical exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
745
7
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 645 publications
(798 citation statements)
references
References 53 publications
38
745
7
8
Order By: Relevance
“…Additionally, a recent report from Varodayan et al [48] demonstrated that seizure leads to a shortening of the cell cycle in DG precursors, suggesting a link between G 1 phase length and seizureinduced proliferation. To address whether Cdk6 plays a role during seizure-induced proliferation, we injected kainic acid (KA) to WT and Cdk6 À/À animals and quantified precursor cell proliferation in the DG 72 hours later, with a protocol that was described previously [49,50]. Of note, we consistently observed a large overlap between Cdk4/6 and Ki-67 expression 72 hours after either NaCl or KA administration (Supporting Information Fig.…”
Section: Seizure-induced Proliferation and Neurogenesis In Cdk6 2/2 Micementioning
confidence: 84%
See 1 more Smart Citation
“…Additionally, a recent report from Varodayan et al [48] demonstrated that seizure leads to a shortening of the cell cycle in DG precursors, suggesting a link between G 1 phase length and seizureinduced proliferation. To address whether Cdk6 plays a role during seizure-induced proliferation, we injected kainic acid (KA) to WT and Cdk6 À/À animals and quantified precursor cell proliferation in the DG 72 hours later, with a protocol that was described previously [49,50]. Of note, we consistently observed a large overlap between Cdk4/6 and Ki-67 expression 72 hours after either NaCl or KA administration (Supporting Information Fig.…”
Section: Seizure-induced Proliferation and Neurogenesis In Cdk6 2/2 Micementioning
confidence: 84%
“…7A-7E). Because seizure has been demonstrated to initially trigger the proliferation of immature/noncommitted precursors [49,50], we then quantified the numbers of GFAP þ /Ki-67 þ and Sox2 þ /Ki-67 þ cells following KA injection. We observed a dramatic increase of the number of GFAP þ and Sox2 þ proliferating precursors, independently of the mouse genotype (Fig.…”
Section: Seizure-induced Proliferation and Neurogenesis In Cdk6 2/2 Micementioning
confidence: 99%
“…IdU was administered over 24 h diluted in drinking water at 0.92 mg/ml. These doses were based on equimolar doses of 50 mg/kg (Llorens‐Martin et al , 2010) and 0.8 mg/ml BrdU (Lugert et al , 2010), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Aging is associated with reduced neurogenesis in the mouse SVZ and SGZ (Encinas et al., 2011; Enwere et al., 2004; Lugert et al., 2010; Luo, Daniels, Lennington, Notti & Conover, 2006), which might lead to decreased olfactory function and cognitive hippocampus‐dependent impairment (Goncalves et al., 2016; Lledo & Valley, 2016). This age‐associated neurogenic decline appears to be caused both by a depletion in the NSPC pool of the aged niche (Ahlenius, Visan, Kokaia, Lindvall & Kokaia, 2009; Bouab, Paliouras, Aumont, Forest‐Berard & Fernandes, 2011; Corenblum et al., 2016; Enwere et al., 2004; Luo et al., 2006; Maslov, Barone, Plunkett & Pruitt, 2004; Molofsky et al., 2006; Stoll et al., 2011) and by the decreased capacity of the remaining NSPCs to sustain proliferation and neuronal differentiation, as revealed by in vitro studies (Ahlenius et al., 2009; Apostolopoulou et al., 2017; Corenblum et al., 2016; Daynac, Morizur, Chicheportiche, Mouthon & Boussin, 2016; Daynac et al., 2014; L'Episcopo et al., 2013; Shi et al., 2017; Zhu et al., 2014).…”
Section: Introductionmentioning
confidence: 99%